ANALYSIS OF FACTORS AFFECTING THE DEMAND FOR BROILER CHICKEN MEAT IN PAMULANG DISTRICT, SOUTH TANGERANG CITY - Elpawati Elpawati; Junaidi Junaidi; Ilham Fachrizal (AGRIBUSINESS JOURNAL, 2022)
Chicken meat is a source of animal food that contains high enough nutrients in the form of protein and energy. Broilers are one of the most popular commodities in the world of livestock agribusiness in Indonesia. In 2021 broiler meat production in South Tangerang City will reach 17,897,290 Kg, but broiler chicken meat production is assisted by farmers from nearby cities and regencies for up to 60% of total production. Pamulang experienced an increase in demand in 2021 with a total of 4,225,286 Kg. The data that will be collected in this research are data on chicken meat consumption in one family, data on egg consumption in one family, data on the purchase price of chicken meat in one purchase, data on the purchase price of eggs in one purchase, income in one family, the number of family members. The characteristics of household consumers in Pamulang District are dominant in buying broiler chicken meat as much as 1-3 Kg per month because it is easy to obtain, household consumers are also more dominant in buying broiler chicken meat at a vegetable shop near their home. The factors that influence the demand for broiler meat are the price of broiler chicken meat, the price of chicken eggs, the number of family members, and family income. There are only 3 of the factors that significantly affect the demand for broiler meat among household consumers in Pamulang District, namely the variable price of broiler meat, the price of chicken eggs and family income, for the variable number of family members has no significant effect on the demand for broiler chicken in household consumers in Pamulang District.